ANALYSIS OF WASTE IN A CANDLE MANUFACTURING PRODUCTION LINE USING WASTE ASSESSMENT MODEL - Teresa Novita; Wilson Kosasih; Ahmad (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2026)
The current state of the manufacturing industry demands that businesses continuously optimize their production processes. In reality, many activities still do not contribute to product added value, potentially leading to various forms of inefficiency. This situation has a negative impact in the form of increased production costs, decreased productivity levels, and extended duration required to complete the production process. The purpose of this study was to detect the categories of waste occurring in the candle production process and to design recommendations for improvements that can be implemented by the company. The study was conducted using Value Stream Mapping (VSM) as a tool for mapping material flows, Process Cycle Efficiency (PCE) to measure the extent to which process efficiency has been achieved, and the Waste Assessment Model (WAM) to determine the dominant waste categories. The research findings indicate that defects are the most common type of waste. The main triggers are unstable temperature settings, inconsistent raw material quantities, and incorrect wick installation. Based on the results of the investigation using the 5 Whys analysis and the 5W+1H approach, the implementation of the 5S and the Kanban system is recommended as concrete steps to reduce waste and encourage increased operational efficiency and product quality.